A STUDY OF SHIPPING ACCIDENTS VALIDATES THE EFFECTIVENESS OF ISM-CODE - Dimitrios X. Kokotos (European Scientific Journal, ESJ, 2013)
The purpose of this paper is to examine human reliability with reference to all accidents involving Greek-flagged ships in restricted waters (ports, canals, straits, anchorages, coastal waters etc) through a 17-years time period (1995-2011). In this context, the effectiveness of enforced International Safety Management Code will be assessed. The data analysis, using a Validation data set (upgrade data over the years from 2007 to 2011), revealed that the implementation of the ISM-Code led to an overall reduction of human-induced accidents in restricted waters. Conclusively, the ISM-Code constitutes an effective policy measure for shipping safety. The results of the analysis reported in the present work can be used by decision makers in companies and international organizations to augment their information in the field of safety policy and management.